Gastrointestinal Bleeding in COVID-19 Patients: A Systematic Review with Meta-Analysis - Giovanni Marasco; Marcello Maida; Gaetano Cristian Morreale; Massimo Licata; Matteo Renzulli; Cesare Cremon; Vincenzo Stanghellini; Giovanni Barbara (Canadian Journal of Gastroenterology and Hepatology)
The novel coronavirus disease 2019 (COVID-19) has been reported to affect the gastrointestinal system with a variety of symptoms, including bleeding. The prevalence of bleeding in these patients remains unclear. The aim of this meta-analysis is to estimate the rate of gastrointestinal bleeding in COVID-19 patients and its association with mortality. MEDLINE and Embase were searched through December 20, 2020. Studies reporting COVID-19 patients with and without gastrointestinal bleeding were included. Estimated prevalence with 95% confidence intervals (CI) was pooled; heterogeneity was expressed as I2. Metaregression analysis was performed to assess the impact of confounding covariates. Ten studies met the inclusion criteria and were included in the analysis. A total of 91887 COVID-19 patients were considered, of whom 534 reported gastrointestinal bleeding (0.6%) [409 (76.6%) upper and 121 (22.7%) lower gastrointestinal bleeding (UGIB and LGIB, resp.)]. The overall pooled gastrointestinal bleeding rate was 5% [95% CI 2–8], with high heterogeneity (I2 99.2%); “small study effect” was observed using the Egger test (p=0.049). After removing two outlier studies, the pooled bleeding rate was 2% [95% CI 0–4], with high heterogeneity (I2 99.2%), and no “small study effect” (p=0.257). The pooled UGIB rate was 1% (95% CI 0–3, I2 98.6%, p=0.214), whereas the pooled LGIB rate was 1% (95% CI 0–2, I2 64.7%, p=0.919). Metaregression analysis showed that overall estimates on gastrointestinal bleeding were affected by studies reporting different sources of bleeding. No significant association between gastrointestinal bleeding and mortality was found. In this meta-analysis of published studies, individuals with COVID-19 were found to be at risk for gastrointestinal bleeding, especially upper gastrointestinal bleeding.